Imitation Of The Song Bareh Solok Through Vocals Of Graphic Improved Students At SLB Waraqil Jannah, West Sumatra. - Saputra, Rizky; Emridawati, Emridawati; Irwan, Irwan; Martarosa, Martarosa (Musica: Journal of Music, 2024)
SLB Waraqil Jannah is a special school in West Sumatra, which has mentally retarded students who have problems with limited speech, slow thinking and communication. This research aims to reveal this problem through the application of imitation learning of the Bareh Solok song and find out the results of this application. This research is of the Qualitative type with a Descriptive Analysis approach, using Constructivism theory, Imitation theory and Learning theory. Data collection techniques: literature study and field study, and data analysis using Milles and Huberman theory: data reduction, data presentation, and drawing conclusions. The results of this research show that Waraqil Jannah SLB students can perform the song Bareh Solok through the vocals of mentally retarded students as a creativity enhancement which was carried out at Mifan Padangpanjang City